2012
DOI: 10.1007/s00345-012-0964-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of preoperative hydronephrosis on the outcome of urothelial carcinoma of the upper urinary tract after nephroureterectomy: the results from a multi-institutional French cohort

Abstract: Preoperative hydronephrosis was not associated with survival. However, among tumours presenting with hydronephrosis, pelvicalyceal tumours appear to have a worse prognosis than ureteral tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 19 publications
1
27
0
Order By: Relevance
“…Prior studies have evaluated HN in cohorts composed of both HG and LG tumors. Several studies individually identified that HN was associated with worse oncologic outcomes (metastasis-free survival, CSS, and overall survival), whereas other studies identified no such associations (Table 5) [8,[11][12][13]15]. Furthermore, the relationship between HN and muscle-invasive disease also varied in several studies [9,10,14].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Prior studies have evaluated HN in cohorts composed of both HG and LG tumors. Several studies individually identified that HN was associated with worse oncologic outcomes (metastasis-free survival, CSS, and overall survival), whereas other studies identified no such associations (Table 5) [8,[11][12][13]15]. Furthermore, the relationship between HN and muscle-invasive disease also varied in several studies [9,10,14].…”
Section: Discussionmentioning
confidence: 87%
“…Presence of HN in UTUC has also been suggested to be associated with advanced pathological stage on final specimen and has been linked to development of cancer metastasis and survival [8][9][10][11][12]. However, confounding studies have identified the contrary [13][14][15]. All prior HN studies evaluated patients with LG and high-grade (HG) UTUCs as 1 cohort.…”
Section: Introductionmentioning
confidence: 95%
“…And it is noteworthy that preoperative hydronephrosis, a potential prognostic predictor discussed in some studies [23][24][25][26], was also found to be an independent predictor of survival. Additionally, we also investigated the association between preoperative pyuria and bladder recurrence following RNU (Supplementary Table S1).…”
Section: Discussionmentioning
confidence: 92%
“…There have been a number of studies focused on the association between the presence of HN and clinicopathological characteristics and prognosis (17,(22)(23)(24)(25)27). The majority of these studies have reported a predictive role of HN in poor pathological outcomes, however, there has been no consensus on the association between HN and poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Ito et al (22) reported that 67 patients (73.6%) exhibited HN in a retrospective study of 91 cases, and validated the correlation between HN and poor pathological outcomes, whilst a higher HN grade was not associated with disease-specific or metastasis-free survival. Bozzini et al (27) conducted a relatively large-scale study with 401 patients, however, HN was present in only 18.4% of patients and the median follow-up period was 26 months. Furthermore, whilst studies by Messer et al (23) and Brien et al (24) demonstrated that HN was associated with muscle-invasive and non-organ confined disease, these studies were lacking in follow-up data.…”
Section: Discussionmentioning
confidence: 99%